Stage IAE Follicular Lymphoma of the Breast: Case Report and Review of the Literature - Raymon Patron; Edward F. Miles (Case Reports in Oncological Medicine)
Primary lymphoma of the breast is a rare entity in the field of oncological medicine and represents <0.5% of all breast malignancies. A definitive diagnosis is obtained by excisional biopsy as the clinical and radiographical presentation is similar to the more common primary breast carcinoma. Unlike primary breast carcinoma, localized radiation therapy is the mainstay of treatment. We report on a case of primary follicular lymphoma of the breast in a 67-year-old Caucasian woman treated with localized radiation as well as coinciding literature review regarding outcomes of different treatment modalities.